2013
DOI: 10.7763/ijcee.2013.v5.774
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of LULU and Median Filter for Image Denoising

Abstract: Abstract-This paper presents a comparison between LULU and Median filters for impulse noise in images. Noise removal from images is always a challenging area of research. Different methods are being used for different image noises such as Wiener filter for Gaussian noise, Frost filter for speckle noise and median filter for impulse noise. LULU filters are widely being used for impulse noise too. LULU filters are nonlinear rank selector operators which are computationally more competent and the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The output is set to this median value with the coordinates of pixel (m,n) and without the smoothing characteristics. The edges and image intensity are not affected in the magnetic resonance images with respect to their gray level intensity [47]. This nonlinear filtering method is used to remove the shot noise from the image without attenuation and median window slides pixels are processed without intensity [48].…”
Section: Methodsmentioning
confidence: 99%
“…The output is set to this median value with the coordinates of pixel (m,n) and without the smoothing characteristics. The edges and image intensity are not affected in the magnetic resonance images with respect to their gray level intensity [47]. This nonlinear filtering method is used to remove the shot noise from the image without attenuation and median window slides pixels are processed without intensity [48].…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, MR image de-noising has become an important purpose in medical imaging particularly the Magnetic Resonance Imaging (MRI). Many de-noising and enhancement techniques are applied on MRI images [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that Image processing is one state of the art tool for introducing objectivity and automation in skin lesion diagnosis. Through image processing techniques, one can segment the lesion from normal skin, can categorize lesions based on features, remove artifacts, and estimate thickness of the lesion through 3D reconstruction [12]. In this way, almost all diagnostic functions that a human can do are also performable by image processing techniques in an objective way.…”
Section: Introductionmentioning
confidence: 99%